1997
DOI: 10.1113/jphysiol.1997.sp021935
|View full text |Cite
|
Sign up to set email alerts
|

Three different Cl‐ channels in the bovine ciliary epithelium activated by hypotonic stress.

Abstract: 1. Hypotonic solution induced transient Cl-channel activity in both pigmented and nonpigmented ciliary epithelial cells in cell-attached patches. 2. The activation time constants for these currents were 63 and 97 s for non-pigmented and pigmented ciliary epithelial (NPCE and PCE) cells, respectively. The currents inactivated during the exposure to hypotonic solution with time constants of 59 and 304 s for NPCE and PCE cells, respectively. 3. Single channel analysis revealed the presence of a low-conductance Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Excitation mapping showed that TRPV4-induced cation influx takes place in the NPE layer but is absent from the PE layer. This is consistent with critical importance of calcium homeostasis and volume regulation in these aqueous fluid-producing cells (2,4,5,32,33,37,(41)(42)(43)(44). The confinement of the agmatine signal to the vicinity of the plasma membrane suggests that potent local cation clearance mechanisms (Na/K ATPases and PMCAs) limit the diffusion of Ca 2+ signals and their spread across the NPE-PE syncytium.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Excitation mapping showed that TRPV4-induced cation influx takes place in the NPE layer but is absent from the PE layer. This is consistent with critical importance of calcium homeostasis and volume regulation in these aqueous fluid-producing cells (2,4,5,32,33,37,(41)(42)(43)(44). The confinement of the agmatine signal to the vicinity of the plasma membrane suggests that potent local cation clearance mechanisms (Na/K ATPases and PMCAs) limit the diffusion of Ca 2+ signals and their spread across the NPE-PE syncytium.…”
Section: Discussionsupporting
confidence: 50%
“…It is therefore noteworthy that NPE and PE layers differ in volume sensing, regulation, and the expression and function of volumeactivated Cl − channels, K + channels, PMCAs, Na/K ATPases, and NKCC transporters (5,33,43,44). The distinctiveness of volume regulatory and Ca 2+ homeostatic apparati is consistent with the strikingly different functions in generation and secretion of aqueous humor (2,4 -dependent activity of Na/K ATPases, the primary determinant of aqueous humor secretion (2,5,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…These channels were similar to those observed in cultured cortical astrocytes from rats [4,49,50] and mice [5][6][7]51] as well as in a rat astrocytic RGCN cell line [52]. In epithelia, the urinary bladder [53], gastric [54], pancreatic [55][56][57], colonic [58][59][60], airway [61][62][63], choroid plexus [64], bile duct [65,66], ciliary [67][68][69], renal [9,19,[70][71][72][73][74][75][76][77][78], vestibular [79], placental [80][81][82][83][84][85][86], ruminal [87] and ovarian [84] epithelial cells were also found to express the maxianion channel with properties similar to those of excitable cells. Resembling maxi-anion channels were also found in fibroblasts [14,…”
Section: Expression Pattern Of the Maxi-anion Channelsupporting
confidence: 58%
“…It has been reported that there were three types of volume-activated Cl Ϫ channels in ciliary epithelial cells and that the expression of these channels was different between the two cell types of the ciliary epithelium (40). Antisense knockdown of MDR1 (35), ClC-3 (36), or pICln (4) gene expression inhibited the volume-activated Cl Ϫ currents.…”
Section: Discussionmentioning
confidence: 99%